Socioeconomic and health factors associated with kindergarten retention in Australian children. (23rd December 2015) - Wong, Evelyn; Steele, Emily; Johnson, Shae; Proimos, Jenny; Batterham, Angela; Nolan, Terry; Waters, Elizabeth
Abstract : Aim: We aimed to identify key socioeconomic and health factors that are associated with a child's likelihood of being retained in kindergarten prior to commencing first year of school in Australian children. Methods: We used data linked from the School Entrant Health Questionnaire administered to children commencing school in 2012 ( N = 42 002). Kindergarten retention here is defined by children accessing a second year of funded kindergarten prior to commencing school. We used logistic regression analysis to estimate the strength of associations between a range of socioeconomic and health factors to the likelihood of kindergarten retention. Results: Of the 25 289 children included in our analysis, 903 (3.6%) had a second year of funded kindergarten prior to commencing school. In comparison, 1680 children out of 42 002 in the Kinder‐School Entrant Health Questionnaire dataset had a second year of funded kindergarten (4.0%). From our final regression model, the highest association was found in children whose parents reported a history of speech and language difficulties (odds ratio 2.25, 95% confidence interval (1.91–2.66)) (adjusting for a range of demographic, health and developmental factors). Similarly, children from an indigenous background were twice as likely to be retained in kindergarten compared with those with a non‐indigenous background (odds ratio 2.06 (1.17–3.64)). Conclusion: This analysis adds to the evidence base that children who are more socially disadvantaged as well as children with health difficulties, particularly speech and language difficulties, are more likely to be retained in kindergarten.